Evaluating the Potential of Fermented Leguminous Plant Leaves as a Fertilizer for Rice (Oryza Sativa) Production - Ibañez Jr., Roger Y.; Velza, Jacob Frederick P.; Pelayo Jr., Cristito C. (Biosaintifika: Journal of Biology & Biology Education, 2023)
Synthetic fertilizers improved rice yield, but they were expensive and reduced soil health. Fermented leguminous plant leaves (FLPL) were natural fertilizers that had a lot of nutrients that plants needed to grow and develop because they were locally available and economical to farmers. This study investigated the effects of fermented leguminous plant leaves as fertilizer for rice. The four treatments were arranged in a Randomized Complete Block Design and replicated three times. Plant height, tillers, grain weight, and economic returns were collected and analyzed using Analysis of Variance (ANOVA). The results showed that the control group that received synthetic fertilizers had significantly (P0.05) taller rice plants compared to the treatment groups. However, among the fermented leguminous leaves, rice plants that received Madre de cacao showed the highest plant height due to its high phosphorus content. The study also found no significant differences (P0.05) in the number of tillers between the treatments, indicating that fermented leguminous leaves can provide the necessary nutrients for crop growth. It was concluded that fermented leguminous leaves can be used as fertilizer to promote eco-friendly rice farming practices. Madre de cacao leaves were recommended as organic fertilizer for rice for at least three months to enhance plant height and overall plant growth. The potential of FLPL, especially from madre de cacao, as an economical alternative to synthetic fertilizers is a breakthrough in rice production. The results demonstrated the potential benefits of using Madre de Cacao leaves as fertilizer to promote eco-friendly rice farming.